The e Impact of Indonesia-Bangladesh Railway Cooperation on the Establishment of Bilateral Preferential Trade Agreements - Muhammad Darley Alfian Pratama; Rizki Rahmadini Nurika (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
This research discusses the railway cooperation between Indonesia and Bangladesh which is motivated by the interest of Bangladesh to revitalize railways and increase the domestic demand for railways. This research aims to find out why the Indonesia-Bangladesh cooperation in the railway sector has a significant impact on the formation of the Indonesia Bangladesh Preferential Trade Agreement (IB-PTA) in 2018. This research using interview and literature study methods. The theory used in this research is the theory of interdependence and economic integration. The conclusion of this research is that the Indonesia Bangladesh railroad cooperation has a significant impact, causing a sense of mutual dependence. The two countries finally agreed to form economic integration in the form of PTA in order to improve the economies of each country.